Identification of Bacterial Pathogens from Nasal Cavity in Cattle with Pneumonia by MALDI-TOF MS - Dinçer, Pelin Fatoş Polat; Yerlikaya, Zeynep; Karagülle, Burcu (My University, 2022)
The aim of our study was to show the etiological spectrum of pathogens in the nasal cavity of cattle \rwith pneumonia using MALDI-TOF MS. The study material consisted of 64 dairy cows between the \rages of 2 and 7 years, 39 calves aged between 30 and 85 days showing pneumonia symptoms \rand 20 healthy dairy cows and calves sampled from 24 farms in different districts of İzmir, Turkey. \rAfter clinical examination of all animals, nasal samples were taken using a swab with Charcoal \rAmies transport medium. The clinical examination revealed that the respiratory rate, heart rate, and \rrectal temperature were statistically higher in cases with pneumonia symptoms than in control \rcases (p<0.001). MALDI-TOF MS isolated 17 different bacteria from the dairy cow samples. The \rmost frequently isolated bacterial pathogens were Escherichia coli (E. coli (32.8%), Staphylococcus \rlentus (S. lentus) (28.1%) and Staphylococcus sciuri (S. sciuri) (21.8%). Of the 11 different bacteria \risolated from calves, the most frequent ones were E. coli (46.1%), S. lentus (41.0%), \rStaphylococcus xylosus (S. xylosus) (7.6%) and S. sciuri (7.6%). Culture and conventional PCR \rmethods were used to determine the presence of Mycoplasma in the samples. In 29 of the samples \rtaken from cattle and calves, Mycoplasma spp. M. bovis was isolated in 24. While S. sciuri (12.5%) \rand E. coli (12.5%) were detected the most among the factors causing mixed infection with M. \rbovis. While these findings reveal the spectrum of pneumonia agents in our region, they show that \rpathogens in the nasal cavity can be detected quickly and reliably with MALDI-TOF MS.
Keywords: Genel ve Dahili Tıp; Mikrobiyoloji; Veterinerlik